SYMBOLIC INTERPRETATIONS IN MEDYA HUS’S POEMS IN ACEHNESE (LINGUISTICA, 2022)
Principally this research attempts to find out the symbols and reasons displayed in Medya Hus‟s Poems in Acehnese. This study was conducted by using descriptive qualitative method. The sources of the data were the poems in „Jameun Internet‟ book by Medya Hus in Acehnese. The instrument for collecting data are documentary sheet. The data were analyzed by using Pierce‟s theory of semiotic. The writer found 22 meanings were displayed in the Medya Hus‟s poems. They were Aki wèt-wèt (3,33%), Budôk (3,33), Engkôut (3,33%), Ujeuen (3,33), Zakéut (3,33%), Teukabo (3,33%), Kayèe Syuruga (3,33%), Syuruga Lapan (3,33%), „Arasy (3,33%), Rabôn (3,33%), Qur‟an ngon Hadis (3,33%), Nuraka (3,33%), Agama (20%), Lampu (3,33), Bohaté (3,33%), Mata Beungah (3,33%), Kapai (3,33%), Syèthan (3,33%), Ratéb (6,7%), Syuruga (10%), Tasbèh (3,33%), Taqwa (3,33%). In the poems contain of different symbols and meaning. Medya Hus almost used the symbols that related to Islamic concept to show the roles of Islam in Aceh and explained the Acehnese culture and society, and nature.